Development of broodstock conditioning-, induced spawning-, and hatchery methods for the South African spotted grunter (Pomadasys commersonnii) - Rakgoale, Amos (Department of Biological Sciences, 2023)
The domestication of candidate marine finfish aquaculture species is an indispensable program to procure undisturbed supply of larvae for research or commercial purposes. The current study focused on a widely distributed haemulid candidate species locally called the spotted grunter (Pomadasys commersonnii). The spotted grunter is a high valued species, described as premier fish with fleshy meat and taste. It is an ideal aquaculture species because it grows fast, can tolerate salinity of less than 1 to 90 %, the females spawn more than once during the spawning period, juveniles of this species can be reared in high stocking density, and accept a supplementary diet (economic pond culture). The current study is a first to experimentally develop efficient procedures for controlled reproduction of captive reared spotted grunter broodstock, and with tested repetitiveness. Broodstock females and males of two years and older were include. Spotted grunter did not spawn spontaneously in captivity, though pre-spawn conditioning of F1 and F2 breeders could be achieved by applying the following developed procedures which include spawning induction: (1) feeding breeders with squid and/or pilchards (3% body mass/day) and rearing them in a fully equipped marine recirculating aquaculture system at the marine research aquarium of the Department of Forestry, Fisheries and the Environment (DFFE) at Sea Point, Cape Town, (2) maintaining a stocking density of about 4 - 7 kg/m³, (3) applying a photothermal program with photoperiod exposure set consistently at 12 Dark: 12 Light (12D: 12L) (250 lux) – with thermal program split in a 3 week consistent exposure setting (24 ± 0.05 ⁰C), followed by 2 day cycles (x3) with temperature fluctuation of ± 5 °C per cycle. Histological examination of the ovaries indicated that final ovarian maturation status was achieved in conditioning programs, but ovulation and spawning needed be induced artificially in captive breeders. Spawning induction was facilitated by finally increasing water temperature from 19 to 24 °C, and finally using Ovaprim® (gonadotropin-releasing hormone analogue [GnRHa]) as decapeptide (spawning inducer (0.25 mℓ/kg). The Ovaprim® was applied intramuscularly (IM) at only 50 % of the prescribe dose (0.5 mℓ/kg). The physical handling, however, resulted in a stress response of non-feeding for about one week. This unavoidable period of prolonged stress in spotted grunter broodstock following artificial induction of spawning, must be considered in broodstock management strategies. The reproductive capacity of spotted grunter broodstock is a function of size and age, since GnRHa-induced broodstock older than four years were predominantly nonresponsive to spawning induction interventions (reproductively dysfunctional). Females in the two to three years age range performed reliably with predictable and highly fecund maximized spawning output success. Young breeders in this age group spawned eggs with gradually increased quantities and consistently high fertilization rates when exposed to the conditioning programs without interruptions. The histology of their ovaries showed cohorts of oocytes at different stages of maturity: perinucleolar stage of the primary growth of the oocyte, primary oocyte, cortical alveoli secondary oocyte, late vitellogenic oocyte and hydrated oocytes. This, together with the spawning frequency data, confirms that spotted grunters are group asynchronized multi-batch spawners. Where synchronized spawners release all their eggs of similar maturity stage and deplete their ovaries fully, asynchronized spawners will not release all their eggs but only those batches that are fully developed to pre-spawn stage. The unreleased premature intraovarian oocytes will develop further in batches and be available as mature eggs following subsequent conditioning programs. The latency time from spawning induction to first spawning activity was about 32 h at 24 ± 0.05 ⁰C. Broodstock conditioning success was marked by a relatively high collective fertilized egg yield (> 97 %) which was indicative that high quality gametes were produced with trial repeated consistency. The collective quantity of spawned eggs was substantively increased when the same breeders were exposed to the mentioned thermal fluctuation program, as compared to a constant temperature exposure only (24 ± 0.05 ⁰C). Fertilized eggs were positively buoyant (floating/pelagic), whilst non-fertilized eggs were negatively buoyant (sinking). The diameter of the fertilized eggs was 1.52 -1.60 mm (mean ± SE = 1.54 ± 0.01 mm, n = 10) and the eggs hatched within about 24 - 26 h after fertilization at 21 ± 0.05 ⁰C. The length of the larvae 5 h after hatching was 2.44 - 2.51 mm (n =10). Larval growth and survival were monitored for the first seven days post-hatch (DPH) under three distinct feeding set-ups with approximately 8000 hatchlings each: (i) clear water (filtered sea water) that served as the control treatment; (ii) algae rich Nannochloropsis oculata water at a final concentration of 500 x 103 -1 x 10 6 cells/mℓ , and (iii) 0. 125 g/ℓ of bentonite clay. These feeding set-ups were exposed to an overhead illumination of 750 lux and maintained at 21 ± 0.05 °C. Mortality rates were high between one and three DPH, and the survival steeply declined from four to six DPH, irrespective of larval density, until ≤ 20 larvae remained at three DPH in all the treatments. At three DPH, the clear water treatment still demonstrated high larval survival of 5198 ± 458.31 compared to 2843 ± 564.33 larvae in tanks of N. oculata and 3092 ± 407.41 larvae from the bentonite clay treatment. At six DPH, the larval survival was approximately 5.1 % for both the clear water and Nannochloropsis treatment groups, whilst survival of the bentonite treated group was slightly better at 8.5 %. The growth rate of the P. commersonnii larvae were not significantly different (p ˃ 0.05) across the treatment groups from hatching to two DPH. Clear water treatment demonstrated superior growth from three DPH until termination (seven DPH) obtaining a final averagelength of 3285 ± 41.32 µm (mean ± SE). While the growth rate was not significantly different (p ˃ 0.05) at three DPH between N. oculata and bentonite treatments, the growth of larvae reared in bentonite clay suspension was significantly more (p < 0.5)than N. oculata at trial termination, achieving respective final lengths of 3106 ± 25.35 µm and 2908 ± 9.20 µm. The development of larval eye pigmentation was first observed three DPH and feeding commenced four DPH in all the treatments. Throughout the rearing trials, the larvae fed close to the surface area, whilst no cannibalism was observed. Inflation of the swim bladder was observed at five DPH, until termination of the rearing trial (seven DPH). The survival of larvae was low in all treatments, and this was attributed to culture contamination with an opportunistic and pathogenic microbial species introduced with the live rotifers into the hatchery, as well as with introduced diluted algae cultures. Microbial contamination persisted in all larval rearing trial. It is very likely that the microbes proliferated in the hatchery tanks as a result of the unavoidable increase in organic material (uneaten food and larval metabolic waste). These aspects deserve intensive investigation in future research. In conclusion, the current study successfully developed procedures for all aspects of controlled and programmable spotted grunter reproduction under captive conditions. Weaned juveniles (21 DPH) could only be produced under high algae density conditions, which act as a probiotic against pathogenic microbes introduced by zooplankton such as rotifers (first feed). The developed hatchery procedures can now be applied in presumptive commercial spotted grunter hatcheries, which can also be utilized for stock recruitment in stock replenishment programs such as for estuaries or species conservation areas.